2018
DOI: 10.3892/ijmm.2018.3781
|View full text |Cite
|
Sign up to set email alerts
|

A proteomic analysis of chemoresistance development via sequential treatment with doxorubicin reveals novel players in MCF‑7 breast cancer cells

Abstract: Breast cancer exhibits the highest incidence of all cancer types and is the 2nd leading cause of cancer mortality in women. Up to 82% of breast cancer patients receive a chemotherapy-containing treatment regimen. However, numerous breast tumors recur within 10 years following an initial response and are frequently resistant to previous therapeutic agents. Thus, to analyze the crucial factors, and whether the development of resistance in tumor cells follows certain patterns, is of great importance. In the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…Despite remarkable advances in early screening and detection of cancer over the past decades, advanced BC remains a threat to both premenopausal, perimenopausal and postmenopausal women globally due to the development of drug resistance in vivo, 23 with potential tumour recurrence following the initial response. 24 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite remarkable advances in early screening and detection of cancer over the past decades, advanced BC remains a threat to both premenopausal, perimenopausal and postmenopausal women globally due to the development of drug resistance in vivo, 23 with potential tumour recurrence following the initial response. 24 …”
Section: Discussionmentioning
confidence: 99%
“…Despite remarkable advances in early screening and detection of cancer over the past decades, advanced BC remains a threat to both premenopausal, perimenopausal and postmenopausal women globally due to the development of drug resistance in vivo, 23 with potential tumour recurrence following the initial response. 24 The current treatment targets to reduce the metastatic potentials of invasive BC cells mainly focus on the inhibition of the proliferation-related and invasion-related pathways, including cell cycle, apoptosis and mitosis through chemotherapy, radiotherapy and surgical interventions. 23 25 26 However, the current therapeutic options for BC lack the ability to fully block the fundamental mechanism associated with cancer invasive disseminations.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, FTIR is able to isolate specific patterns or chemical fingerprints for distinguishing parental and drug‐resistant cells . Proteomic techniques have also been widely used to determine drug mechanisms . Before samples are subjected to mass spectroscopy, samples must be accurately prepared using multiple steps in laboratory conditions.…”
Section: Introductionmentioning
confidence: 99%
“…These resistant cell lines were characterized by metabolic reprogramming that may provide novel therapeutic opportunities for treating chemoresistant TNBCs. Other studies of acute chemotherapy treatment of MCF7 cells revealed increased expression of proteins related to apoptosis signaling and redox homeostasis ( 110 ). Serial analyses of pre- and post-chemotherapy TNBC biopsies has nominated putative drivers and suppressors of adaptive survival programs in post-chemotherapy residual disease.…”
Section: In Vitro Models Of Therapy Resistance—2dmentioning
confidence: 99%